L’État ottoman et la guerre de Trente Ans, les dommages à long terme de la neutralité - Jean-Louis Bacqué-Grammont (Cahiers Balkaniques)
The war between Ottomans and Habsburgs from 1593 to 1606 looks noteworthy not only because it had been going on for many years, but also because they were equally matched forces: each side alternatively took the advantage over the other, but none of them was conclusive. In consequence, peace was searched with eagerness by both sides. When it finally ended more than half a century later, the Ottomans were in difficulty right from the first battles and, in spite of their great power, they could not find back their preceding successes. What had happened in the meantime? We shall attend here to underline the cost of their lack of interest towards the Thirty Years War (1618-1648): after that, new weapons and the ways of using them, everything in Western Europe had changed concerning the art of war and it seems that nothing of these new conditions was known on the shore of the Bosphorus.